2021
DOI: 10.3399/bjgp.2020.1098
|View full text |Cite
|
Sign up to set email alerts
|

The Fast Track FIT study: diagnostic accuracy of faecal immunochemical test for haemoglobin in patients with suspected colorectal cancer

Abstract: Background: The faecal immunochemical test (FIT) is now available to support clinicians in the assessment of patients at low risk of colorectal cancer (CRC) and within the Bowel Cancer Screening Programme. Aim: To determine the diagnostic accuracy of FIT for CRC and clinically significant disease in patients referred because they were judged by their GP to fulfil NICE NG12 criteria for suspected CRC. Design and Setting: Patients referred from primary care with suspected CRC, meeting NG12 criteria, to 12 second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 43 publications
0
38
1
Order By: Relevance
“…Bailey et al 10 found 33% were detected at early stage when using FIT in those that satisfied DG30 criteria specifically. Turvill et al 29 Other studies have shown obstructing tumours and higher stage CRC are also common in FIT 'negative' CRC.…”
Section: Fit In Primary Care Vs No Fitmentioning
confidence: 96%
See 1 more Smart Citation
“…Bailey et al 10 found 33% were detected at early stage when using FIT in those that satisfied DG30 criteria specifically. Turvill et al 29 Other studies have shown obstructing tumours and higher stage CRC are also common in FIT 'negative' CRC.…”
Section: Fit In Primary Care Vs No Fitmentioning
confidence: 96%
“…In summary, a meta-analysis informing these guidelines61 and four prior meta-analyses of over 48 000 patients, which include the largest three studies from NICE FIT, qFIT and the York groups on FIT diagnostic accuracy reported an FIT sensitivity for CRC in symptomatic patients to be greater than 87% at a threshold of 10 µg/g28 29 62 (table 1). Therefore, based on the studies reviewed in this section, FIT should be considered in patients presenting with lower GI symptoms irrespective of their nature, to support referral or triage to appropriate investigations if there are concerns about a cancer diagnosis.…”
Section: Diagnostic Accuracy Of Fit For Crc In People With Suspected ...mentioning
confidence: 99%
“…In 2017 the National Institute of Health and Care Excellence (NICE) recommended faecal immunochemical testing (FIT) for the detection of CRC in patients with low risk symptoms 7. Subsequently, several large trials have suggested that FIT also performs well in patients with high-risk symptoms for CRC (87%–94% sensitivity, 80%–89% specificity, 12%–18% positive predictive value (PPV) and 99% negative predictive value (NPV) at a threshold of 10 µgHb/g 4 8–13. However, given the prevalence of CRC in patients presenting to primary care, up to 10% of patients with CRC will not be detected at a threshold of 10 µgHb/g,4 11–13 raising concerns about how the risk associated with managing this group of patients should be managed.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data has proven the utility of FIT in symptomatic patients with sensitivity and specificity reportedly ranging from 85 to 100% and 56 to 91% respectively for colorectal cancer detection at a threshold of ≥ 10 µg Hb/g faeces [8][9][10][11][12][13][14][15]. FIT has proven equally valid in determining cancer risk in patients meeting high risk (NG12) or low risk (DG30) symptom criteria [6,8,16], and in patients with and without rectal bleeding [17]. Most studies to date have examined such FIT programmes and only included referred patients.…”
Section: Introductionmentioning
confidence: 99%